Polymerizable composition, adhesive, sealing material, cured product, semiconductor device, and electronic component
Patent Information
- Application Number
- CN202580021616.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-26
- Publication Date
- 2026-10-27
AI Technical Summary
[0030]根据本发明的方式,可以提供能够抑制渗溢现象的、至少为光固性或热固性的聚合性组合物、包含该聚合性组合物的粘接剂或密封材料、它们经过固化而得的固化物、以及包含该固化物的半导体装置或电子部件。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to polymeric compositions, adhesives or sealants comprising the polymeric compositions, cured products thereof, semiconductor devices and electronic components comprising the cured products. Background Technology
[0002] Currently, adhesives and sealants containing curable resin compositions are frequently used in the assembly and installation of components used in semiconductor devices, such as semiconductor chips, to maintain reliability and other purposes.
[0003] The development of curable resin compositions capable of achieving light curing and / or low-temperature curing is underway. For example, Patent Documents 1 and 2 disclose a cationic curable resin composition with both light curing and low-temperature curing properties.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Re-evaluation No. 2017 / 094584
[0007] Patent Document 2: Japanese Patent Application Publication No. 2021-147584 Summary of the Invention
[0008] In the assembly of semiconductor modules, overflow has become a problem. Overflow refers to the phenomenon where unreacted components seep out of the adhesive coating or cured product over time when adhesives containing curable resin compositions are used to fix and bond components. Sometimes, the seeping component itself is also referred to as "overflow." Sometimes, overflow can come into contact with metal wiring on the substrate, causing electrical malfunctions and reducing the reliability of the semiconductor module. In particular, internal overflow originating from uncured portions of the adhesive tends to develop further when the adhesive coating is left at room temperature and / or during heat curing, with an increasing overflow length.
[0009] In recent years, electronic components such as semiconductor chips have been increasingly required to be miniaturized or highly integrated, resulting in shorter distances to the wiring sections surrounding these components. In semiconductor modules incorporating such miniaturized or highly integrated electronic components, there is an increased risk of leakage contact with the wiring sections due to leakage phenomena.
[0010] Therefore, the object of the present invention is to provide polymeric compositions and adhesives that are at least photocurable or thermocurable and capable of suppressing leakage.
[0011] Specific means for solving the above-mentioned problems are as follows. The present invention includes polymeric compositions, adhesives or sealants, cured products, and semiconductor devices or electronic components in the following ways.
[0012] [1] A polymeric composition comprising:
[0013] (A) Cationic polymeric compounds,
[0014] (B) Acid-producing agents, and
[0015] (C) A modified polydimethylsiloxane that satisfies at least one of the following characteristics (a), (b), and (c):
[0016] (a) Organic substituents containing COOH groups are directly bonded to polydimethylsiloxane, or are bonded to polydimethylsiloxane through linking groups;
[0017] (b) An organic substituent containing an OH group and, where appropriate, an ether group, is directly bonded to polydimethylsiloxane or bonded to polydimethylsiloxane via a linking group, wherein, in the case of an ether group, the ratio of the number of polypropylene glycol repeating units in the organic substituent to the number of polyethylene glycol repeating units is less than 0.3.
[0018] (c) Detected in deuterated chloroform 1 In the H NMR spectrum, a signal is present in the ranges of 0.3 to -0.3 ppm and 4.4 to 3.2 ppm, a signal is present or absent in the range of 1.25 to 0.95 ppm, and a signal that disappears due to the addition of D2O is present in the range of 13 to 0 ppm. Furthermore, the value calculated using the following formula (1) is less than 0.3:
[0019] Equation (1): [(integral value of signal in the range of 1.25 to 0.95 ppm) / 3] / {[(integral value of signal in the range of 4.4 to 3.2 ppm) - (integral value of signal in the range of 1.25 to 0.95 ppm)] / 4}.
[0020] [2] According to the polymerizable composition described in [1] above, wherein the cationic polymerizable compound (A) above comprises a compound having an epoxy group and a compound having an oxetyl group.
[0021] [3] According to the polymerizable composition described in [1] or [2] above, wherein the content of the modified polydimethylsiloxane (C) above is 0.01 to 5% by mass relative to the total mass of the polymerizable composition.
[0022] [4] The polymerizable composition according to any one of [1] to [3] above further comprises (D) filler.
[0023] [5] The polymeric composition according to any one of [1] to [4] above, wherein the components (A) to (C) are configured to be contained in a single container.
[0024] [6] The polymeric composition according to any one of [1] to [4] above, wherein the components (A) to (C) are disposed in two or more containers.
[0025] [7] An adhesive or sealant comprising the polymeric composition described in any one of [1] to [6] above.
[0026] [8] The adhesive or sealing material described in [7] above is used for fixing, bonding or protecting the optical sensor module or the components constituting it.
[0027] [9] A cured product obtained by curing the polymeric composition described in any one of [1] to [6] above, or the adhesive or sealant described in [7] or [8] above.
[0028]
[10] A semiconductor device or electronic component comprising the cured material described in [9] above.
[0029]
[11] The semiconductor device or electronic component described in
[10] above is an optical sensor module.
[0030] According to the present invention, a polymeric composition, at least photocurable or thermocurable, capable of suppressing leakage, an adhesive or sealant comprising the polymeric composition, a cured product thereof, and a semiconductor device or electronic component comprising the cured product can be provided. Detailed Implementation
[0031] [Polymerizable Composition]
[0032] As one aspect of the present invention, the polymeric composition comprises:
[0033] (A) Cationic polymeric compounds,
[0034] (B) Acid-producing agents, and
[0035] (C) A modified polydimethylsiloxane that satisfies at least one of the following characteristics (a), (b), and (c):
[0036] (a) Organic substituents containing COOH groups are directly bonded to polydimethylsiloxane, or are bonded to polydimethylsiloxane through linking groups;
[0037] (b) An organic substituent containing an OH group and, where appropriate, an ether group, is directly bonded to polydimethylsiloxane or bonded to polydimethylsiloxane via a linking group, wherein, in the case of an ether group, the ratio of the number of polypropylene glycol repeating units in the organic substituent to the number of polyethylene glycol repeating units is less than 0.3.
[0038] (c) Detected in deuterated chloroform 1 In H NMR, a signal is present in the ranges of 0.3 to -0.3 ppm and 4.4 to 3.2 ppm, a signal is present or absent in the range of 1.25 to 0.95 ppm, and a signal that disappears due to the addition of D2O is present in the range of 13 to 0 ppm, and the value calculated by the following formula (1) is less than 0.3:
[0039] Equation (1): [(integral value of signal in the range of 1.25 to 0.95 ppm) / 3] / {[(integral value of signal in the range of 4.4 to 3.2 ppm) - (integral value of signal in the range of 1.25 to 0.95 ppm)] / 4}.
[0040] According to this method, a polymeric composition, at least photocurable or thermocurable, capable of suppressing leakage can be provided.
[0041] (A) Cationic polymeric compounds
[0042] The polymerizable composition of this method comprises (A) a cationic polymerizable compound (hereinafter also referred to as "component (A)"). Examples of the cationic polymerizable compound (A) include compounds having an epoxy group, compounds having an oxetyl group, compounds having a vinyl ether group, compounds having other cationic polymerizable groups, and compounds having these cationic polymerizable groups in any combination, but are not limited to them. In one embodiment, the cationic polymerizable compound preferably comprises a compound having an epoxy group and a compound having an oxetyl group.
[0043] In this specification, a compound having an epoxy group is a compound having at least one epoxy group in its molecule, also referred to as an epoxy compound. Examples include monofunctional epoxy compounds having one epoxy group and polyfunctional epoxy compounds having two or more epoxy groups. In this embodiment, the epoxy compound preferably comprises at least a polyfunctional epoxy compound, but may also comprise a combination of polyfunctional and monofunctional epoxy compounds. Epoxy compounds can be broadly classified according to the type of their skeleton into epoxy compounds with an aromatic ring skeleton, aliphatic epoxy compounds, and alicyclic epoxy compounds.
[0044] In this specification, a compound having an oxetane group is a compound having at least one oxetane ring (e.g., 3-oxetane) within its molecule, also referred to as an oxetane compound. In one embodiment, the oxetane compound preferably has 1 to 6 oxetane groups within its molecule, more preferably 1 to 2 oxetane groups within its molecule.
[0045] In this specification, a compound having a vinyl ether group is a compound having at least one vinyl ether group in its molecule.
[0046] Specific examples of cationic polymerizable compounds include glycidyl ethers of tetra(hydrophenyl)alkane, glycidyl ethers of tetrahydroxybenzophenone, epoxidized polyvinylphenol, p-tert-butylphenyl glycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, n-butyl glycidyl ether, and 2-ethylhexyl glycidyl ether. Oil ether, 1,2-epoxytetradecane, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexane carboxylate, 6-methyl-3,4-epoxycyclohexylmethyl-6-methyl-3,4-epoxycyclohexane carboxylate, 3,4-epoxy-3-methylcyclohexylmethyl-3,4-epoxy-3-methylcyclohexane carboxylate, 3,4-epoxy-5-methylcyclohexylmethyl-3,4-epoxy-5-methylcyclohexane carboxylate, bis(3,4-epoxycyclohexylmethyl) adipic acid, 3,4-epoxy-6-methyl Cyclohexane carboxylate, methylene bis(3,4-epoxycyclohexane), propane-2,2-diyl-bis(3,4-epoxycyclohexane), 2,2-bis(3,4-epoxycyclohexyl)propane, dicyclopentadiene diester, ethylene bis(3,4-epoxycyclohexane carboxylate), limonene diester (1,2:8,9-diepoxylimonene), (3,3',4,4'-diepoxy)bicyclohexyl, dioctyl hexahydrophthalate, di-2-ethylhexyl hexahydrophthalate, 1-epoxyethyl-3,4-epoxycyclohexane, 1,2-epoxy-2-epoxyethylcyclohexane, 1,2-Epoxy-4-vinylcyclohexane, α-pinene oxide, 1,2-bis(hydroxymethyl)-1-butanol 1,2-epoxy-4-(2-epoxyethylene)cyclohexane adduct, epoxidized polybutadiene, compounds in which part or all of the double bonds of styrene-butadiene copolymers are epoxidized, bis[1-ethyl(3-oxetane)] methyl ether (also known as (3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane)), phenylenediethylene dioxetane, 4,4'-bis[3-ethyl-(3-oxetane)methoxymethyl]biphenyl, 1,4-Bis(3-ethyl-3-oxetane-butylmethoxy)methylbenzene, (bis[(3-ethyl-3-oxetane-butyl)methyl]isophthalate), 3-ethyl-3-hydroxymethyloxetane, 2-ethylhexyloxetane, (3-ethyloxetane-3-yl)methyl methacrylate, 3-ethyl-3-[(2-ethylhexyloxy)methyl]oxetane, 3-ethyl-3-(4-hydroxybutyl)oxymethyloxetane, 3-ethyl-3-phenoxymethyloxetane, oxetane-butylsilsesquioxane, 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, Phenolic linear phenolic oxetane, 1,4-butanediol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, 2-ethylhexyl vinyl ether, cyclohexyl vinyl ether, 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether, 2-(2-ethyleneoxyethoxy)ethyl acrylate, 2-(2-ethyleneoxyethoxy)ethyl methacrylate, 1,4-cyclohexanediethanol monovinyl ether, 1,4-cyclohexanediethanol divinyl ether, etc., but not limited to these.
[0047] Commercially available cationic polymerizable compounds include: EPICLON (registered trademark) 850, 850-S, EXA-850CRP, and EXA-8067 manufactured by DIC Corporation; AER9000 manufactured by Asahi Kasei Corporation; EP-4000S, EP-4003S, and EP-4010S manufactured by ADEKA Corporation; and EPICLON (registered trademark) 830-S manufactured by DIC Corporation. EXA-830LVP, EXA-835LV; EPICLON (registered trademark) HP-4032D, HP-720H manufactured by DIC Corporation; EPICLON (registered trademark) N-740, N-770 manufactured by DIC Corporation; EPICLON (registered trademark) N-660, N-670, N-655-EXP-S manufactured by DIC Corporation; ADEKA manufactured by ADEKA Corporation. GLYCIROL (registered trademark) ED-509E, ED-509S; OPP-G manufactured by Sanko Chemical Co., Ltd.; EPOLITE 100MF manufactured by Kyoei Chemical Co., Ltd.; AER-9000 manufactured by Asahi Kasei Corporation; jER YX7400N manufactured by Mitsubishi Chemical Co., Ltd.; jER YX8000 manufactured by Mitsubishi Chemical Co., Ltd.; CELLOXIDE (registered trademark) 2021P manufactured by Daicel Co., Ltd.; CELLOXIDE (registered trademark) 8010 manufactured by Daicel Co., Ltd.; EHPE3150 manufactured by Daicel Co., Ltd.; EPOLEAD manufactured by Daicel Co., Ltd. PB; EPOFRIEND manufactured by Daicel Co., Ltd.; HiREM-1 and HiREM-2 manufactured by Shikoku Chemical Co., Ltd.; OXT-191 manufactured by Toa Synthetic Co., Ltd.; OXT-221 manufactured by Toa Synthetic Co., Ltd.; PHOX manufactured by Toa Synthetic Co., Ltd., etc., but not limited to them.
[0048] Cationic polymerizable compounds can be used in combination of any one type or two or more types.
[0049] The cationic polymeric group equivalent of the cationic polymeric compound is preferably 90-1000 g / eq, more preferably 120-800 g / eq, and even more preferably 150-500 g / eq.
[0050] From the viewpoint of preparing polymerizable compositions and their dispensing properties, component (A) is preferably found to have a viscosity of 0.001 to 100 Pa·s. It should be noted that, in this specification, viscosity refers to a value obtained by measuring the viscosity using an appropriate viscometer at a measurement temperature of 25°C, within the specified viscosity range.
[0051] Regarding the content of component (A), from the viewpoint of the adhesive strength of the polymeric composition, it is preferably 10 to 95% by mass relative to the total mass of the polymeric composition, more preferably 20 to 90% by mass.
[0052] (B) Acid-producing agent
[0053] The polymerizable composition of this method comprises (B) an acid-generating agent (hereinafter also referred to as "component (B)"). In this specification, the acid-generating agent generates an acid as an active species under the action of light or heat, causing the cationic polymerizable compound to polymerize. Examples of acid-generating agents include BF4. - SbF6 - AsF6 - B(C6F5)4 - Ga(C6F5)4 - C(CF3SO2)3 - 、[P(R 1 ) a F 6-a ] - 、[C(R 1 SO2)3] - , or [N(R)] 1 SO2)2] - (where R) 1 Each is an alkyl group in which at least a portion of the hydrogen atom is replaced by a fluorine atom, where a is an integer from 0 to 5, and when a is an integer greater than 2, there are multiple R groups. 1 They can be the same or different from each other. ) and various onium salts, which are counter anions and have iodonium cations, sulfonium cations, ammonium cations, and phosphonium cations as cations.
[0054] Examples of iodonium ions that can be cited as iodonium ions include diphenyliodonium, di-p-tolyliodonium, bis(4-dodecylphenyl)iodonium, bis(4-methoxyphenyl)iodonium, (4-octoxyphenyl)phenyliodonium, bis(4-decoxyphenyl)iodonium, 4-(2-hydroxytetradecoxy)phenylphenyliodonium, 4-isopropylphenyl(p-tolyl)iodonium, and 4-isobutylphenyl(p-tolyl)iodonium.
[0055] Examples of matte ions include:
[0056] Triphenylsulfonium, tris(p-tolyl)sulfonium, tris(o-tolyl)sulfonium, tris(4-methoxyphenyl)sulfonium, 1-naphthyldiphenylsulfonium, 2-naphthyldiphenylsulfonium, tris(4-fluorophenyl)sulfonium, tris(1-naphthyl)sulfonium, tris(2-naphthyl)sulfonium, tris(4-hydroxyphenyl)sulfonium, 4-(phenylthio)phenyldiphenylsulfonium, 4-(p-tolylthio)phenylbis(p-tolyl)sulfonium, 4-(4-methoxyphenylthio)phenylbis(4-methoxyphenyl)sulfonium, 4-(phenylthio)phenylbis(4-fluorophenyl)sulfonium, 4-(phenylthio)phenylbis(4-methoxyphenyl)sulfonium, 4-(phenylthio)phenylbis(4-methoxyphenyl)sulfonium, 4-(phenylthio)phenylbis(4-methoxyphenyl)sulfonium, 4-(phenylthio) )Phenyl di(p-tolyl)sulfonium, [4-(4-biphenylthio)phenyl]-4-biphenylphenylsulfonium, [4-(2-thioxanthonethio)phenyl]diphenylsulfonium, bis[4-(diphenylsulfonium)phenyl] sulfide, bis[4-{bis[4-(2-hydroxyethoxy)phenyl]sulfonium}phenyl] sulfide, bis{4-[bis(4-fluorophenyl)sulfonium]phenyl} sulfide, bis{4-[bis(4-methylphenyl)sulfonium]phenyl} sulfide, bis{4-[bis(4-methoxyphenyl)sulfonium]phenyl} sulfide, 4-(4-benzoyl-2-chlorophenylthio)phenylbis(4-fluoro)sulfonium 4-(4-benzoyl-2-chlorophenylthio)phenyl diphenylsulfonium, 4-(4-benzoylphenylthio)phenyl bis(4-fluorophenyl)sulfonium, 4-(4-benzoylphenylthio)phenyl diphenylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracene-2-yldi(p-tolyl)sulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracene-2-yldiphenylsulfonium, 2-[(di-p-tolyl)sulfonium]thioxanthone, 2-[(diphenyl)sulfonium]thioxanthone, 4-(9-oxo-9H-thioxanth-2-yl)thio Phenyl-9-oxo-9H-thioxanth-2-ylphenylsulfonium, 4-[4-(4-tert-butylbenzoyl)phenylthio]phenyl di(p-tolyl)sulfonium, 4-[4-(4-tert-butylbenzoyl)phenylthio]phenyl diphenylsulfonium, 4-[4-(benzoylphenylthio)]phenyl di(p-tolyl)sulfonium, 4-[4-(benzoylphenylthio)]phenyl diphenylsulfonium, 5-(4-methoxyphenyl)thianthanethium, 5-phenylthianthanethium, 5-tolylthianthanethium, 5-(4-ethoxyphenyl)thianthanethium, and 5-(2,4,6-trimethylphenyl)thianthanethium, etc., are triarylsulfoniums.
[0057] Diphenylbenzoylmethylsulfonium, diphenyl-4-nitrobenzylmethylsulfonium, diphenylbenzylsulfonium, and diphenylmethylsulfonium and other diarylsulfonium compounds,
[0058] Phenylacetyl methyl benzyl sulfonium, 4-hydroxyphenyl methyl benzyl sulfonium, 4-methoxyphenyl methyl benzyl sulfonium, 4-acetylcarbonyloxyphenyl methyl benzyl sulfonium, 4-hydroxyphenyl(2-naphthylmethyl)methyl sulfonium, 2-naphthylmethyl benzyl sulfonium, 2-naphthylmethyl(1-ethoxycarbonyl)ethyl sulfonium, phenyl methyl benzoyl methyl sulfonium, 4-hydroxyphenyl methyl benzoyl methyl sulfonium, 4-methoxyphenyl methyl benzoyl methyl sulfonium, 4-acetylcarbonyloxyphenyl methyl benzoyl methyl sulfonium, 2-naphthylmethyl benzoyl methyl sulfonium, 2-naphthyloctadecylbenzoyl methyl sulfonium, and 9-anthraylmethylbenzoyl methyl sulfonium, etc., are monoaryl sulfonium compounds.
[0059] Dimethylbenzoylmethylsulfonium, benzoylmethyltetrahydrothiophenonium, dimethylbenzylsulfonium, benzyltetrahydrothiophenonium, and trialkylsulfonium such as octadecylmethylbenzoylmethylsulfonium.
[0060] Examples of ammonium cations include N,N-dimethylpyrrolidineonium, N-ethyl-N-methylpyrrolidineonium, and N,N-diethylpyrrolidineonium; N,N'-dimethylimidazolineonium, N,N'-diethylimidazolineonium, N-ethyl-N'-methylimidazolineonium, 1,3,4-trimethylimidazolineonium and 1,2,3,4-tetramethylimidazolineonium; tetrahydropyrimidineonium such as N,N'-dimethyltetrahydropyrimidineonium; and N,N'-dimethyl... Morpholinium, N,N'-diethylpiperidine, N-methylpyridinium, N-benzylpyridinium and N-benzoylmethylpyridinium, N,N'-dimethylimidazolium, N-methylquinolineium, N-benzylquinolineium and N-benzoylmethylquinolineium, N-methylisoquinolineium, benzylbenzothiazolineium and benzoylmethylbenzothiazolineium, benzyl acridineium and benzoylmethyl acridineium, etc.
[0061] Examples of phosphonium cations include tetraphenylphosphonium, tetra(p-tolyl)phosphonium, tetra(2-methoxyphenyl)phosphonium, tetra(3-methoxyphenyl)phosphonium and tetra(4-methoxyphenyl)phosphonium, triphenylbenzylphosphonium, triphenylbenzoylmethylphosphonium, triphenylmethylphosphonium and triphenylbutylphosphonium, triethylbenzylphosphonium, tributylbenzylphosphonium, tetraethylphosphonium, tetrabutylphosphonium, tetrahexylphosphonium, triethylbenzoylmethylphosphonium and tributylbenzoylmethylphosphonium, and other tetraalkylphosphonium.
[0062] Specific examples of iodonium salt-based acid-producing agents include:
[0063] Diphenyliodonium hexafluoroarsenate, di(4-chlorophenyl)iodonium hexafluoroarsenate, di(4-bromophenyl)iodonium hexafluoroarsenate, and phenyl(4-methoxyphenyl)iodonium hexafluoroarsenate are used as photoacid-generating agents for arsenate-based iodonium salts;
[0064] 4-Methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tri(pentafluoroethyl)trifluorophosphate (e.g., IK-1 manufactured by San-Apro Corporation), 4-methylphenyl-4-(2-methylpropyl)phenyliodonium hexafluorophosphate (e.g., IRGACURE 250 manufactured by BASF Corporation), bis(C 10~14 (-alkylphenyl) iodonium hexafluorophosphate (such as WPI-113 manufactured by Fujifilm and Kojun Chemical Co., Ltd.) are used as photo-acid-generating agents of phosphate-based iodonium salts (here, IK-1 manufactured by San-Apro Co., Ltd. can also be used as a thermal acid-generating agent).
[0065] 4-Methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate (such as WPI-116 manufactured by Fujifilm and Kojun Pharmaceutical Co., Ltd.) are used as photoacid-generating agents of antimonate-based iodonium salts;
[0066] IK-1FG (manufactured by San-Apro Corporation) and others are used as photo-acid generators for gallium-based iodonium salts (here, IK-1FG can also be used as a thermal acid generator).
[0067] 4-Methylphenyl-4-(1-methylethyl)phenyliodonium tetra(pentafluorophenyl)borate, 4-isopropyl-4'-methyldiphenyliodonium tetra(pentafluorophenyl)borate (e.g., BLUESIL (registered trademark) PI 2074 manufactured by ELKEM SILICONES) are used as photoacid-generating agents of borate-based iodonium salts, but are not limited to them.
[0068] Specific examples of sulfonium salt-based acid-generating agents include photo-acid-generating agents for borate-based sulfonium salts (products manufactured by San-Apro Co., Ltd.: CPI-110B, CPI-310B, CPI-410B, etc.), photo-acid-generating agents for phosphate-based sulfonium salts (products manufactured by San-Apro Co., Ltd.: CPI-210S, VC-1S, CPI-410S, etc.), thermal acid-generating agents for phosphate-based sulfonium salts (products manufactured by San-Apro Co., Ltd.: TA-100, etc.), photo-acid-generating agents for gallium-based sulfonium salts (products manufactured by San-Apro Co., Ltd.: CPI-310FG, VC-1FG, etc.), and thermal acid-generating agents for gallium-based sulfonium salts (products manufactured by San-Apro Co., Ltd.: TA-100FG, etc.), but are not limited to these.
[0069] Specific examples of ammonium salt acid-producing agents include thermal acid-producing agents of borate-based quaternary ammonium salts (such as CXC-1821 manufactured by King Industries, Inc.), but are not limited to these.
[0070] In this method, the content of acid-producing agent (B) in the polymerizable composition is preferably 0.1 to 10% by mass relative to the total mass of the polymerizable composition, more preferably 0.3 to 8% by mass, and even more preferably 0.5 to 5% by mass. The content of acid-producing agent (B) in the polymerizable composition is preferably 0.1 to 30% by mass relative to the total mass of component (A), more preferably 0.5 to 20% by mass, and even more preferably 1 to 15% by mass.
[0071] (C) Modified polydimethylsiloxane
[0072] The polymerizable composition of this method comprises (C) modified polydimethylsiloxane (hereinafter also referred to as "component (C)"). In this method, (C) modified polydimethylsiloxane satisfies at least one of the following characteristics (a), (b) and (c).
[0073] (a) An organic substituent containing a COOH group is directly bonded to polydimethylsiloxane, or is bonded to polydimethylsiloxane through a linking group.
[0074] (b) An organic substituent containing an OH group and, where appropriate, an ether group, is directly bonded to polydimethylsiloxane or bonded to polydimethylsiloxane via a linking group, wherein, in the case of an ether group, the ratio of the number of polypropylene glycol repeating units in the organic substituent to the number of polyethylene glycol repeating units is less than 0.3.
[0075] (c) Detected in deuterated chloroform 1 In the H NMR spectrum, there is a signal in the range of 0.3 to -0.3 ppm and 4.4 to 3.2 ppm, there is or no signal in the range of 1.25 to 0.95 ppm, there is a signal that disappears due to the addition of D2O in the range of 13 to 0 ppm, and the value calculated by the following formula (1) is less than 0.3.
[0076] Equation (1): [(Integral value of the signal in the range of 1.25 to 0.95 ppm) / 3] / {[(Integral value of the signal in the range of 4.4 to 3.2 ppm) - (Integral value of the signal in the range of 1.25 to 0.95 ppm)] / 4}
[0077] More specifically, modified polydimethylsiloxanes have structures in which organic substituents as modifying groups are introduced directly or interspersed between alkyl, alkylene, or other linking groups on the side chains and / or ends of the polydimethylsiloxane backbone formed by repeating dimethylsiloxane units represented by the following formula:
[0078] [Chemistry 1]
[0079]
[0080] Here, "introducing organic substituents into the side chains of the polydimethylsiloxane backbone" means that a portion of the methyl group in the polydimethylsiloxane backbone is replaced with an organic substituent. "Introducing organic substituents into the ends of the polydimethylsiloxane backbone" means that the ends of the polydimethylsiloxane backbone (e.g., methyl groups or -OSi(CH3)3) are replaced with organic substituents. The location of the modifying group in the modified polydimethylsiloxane can be any position on the side chain, at the end (single-terminal or double-terminal), or both. Furthermore, the modified polydimethylsiloxane also includes bimeric polydimethylsiloxanes. The degree of polymerization (the number of repeating units in dimethylsiloxane) of the modified polydimethylsiloxane is not particularly limited, but is, for example, 3 or more, preferably 5 or more.
[0081] In the modified polydimethylsiloxane of feature (a) above, the organic substituent contains a COOH group.
[0082] Examples of modified polydimethylsiloxanes containing COOH groups as organic substituents include products marketed under names such as carboxyl-modified polydimethylsiloxanes or carboxyl-modified silicones. Examples of such commercially available products include those sold by Shin-Etsu Chemical Co., Ltd. under names such as X-22-3701E, X-22-162C, and X-22-3710, but these are not the only examples.
[0083] The presence or absence of the C=O stretching vibration at approximately 1715 cm⁻¹ originating from carboxylic acids can be observed by Fourier transform infrared spectroscopy (FT-IR) of modified polydimethylsiloxane. -1 The IR spectrum was used to confirm whether the organic substituents of the modified polydimethylsiloxane contained COOH groups.
[0084] In the modified polydimethylsiloxane of feature (b) above, the organic substituent contains an OH group and, depending on the case, an ether group. When the organic substituent contains an ether group, the ratio of the number of polypropylene glycol (PPG) repeating units to the number of polyethylene glycol (PEG) repeating units in the organic substituent is less than 0.3. In feature (b), examples of ether groups that may be present in the organic substituent include polyethylene glycol groups and polypropylene glycol groups. In feature (b), when the organic substituent contains an ether group, the ratio of the number of polypropylene glycol repeating units to the number of polyethylene glycol repeating units is preferably less than 0.1, more preferably less than 0.01 (i.e., the organic substituent substantially does not contain polypropylene glycol repeating units). In one embodiment, the ratio of the number of polypropylene glycol repeating units to the number of polyethylene glycol repeating units may be 0.
[0085] Examples of modified polydimethylsiloxanes whose organic substituents include OH groups but not ether groups include products marketed as methanol-modified polydimethylsiloxanes or methanol-modified silicones. Examples of such commercially available products include those sold by Shin-Etsu Chemical Co., Ltd. under the names X-22-4039, X-22-4015, KF-6000, KF-6001, KF-6002, KF-6003, X-22-170BX, and X-22-170DX, but these are not the only examples.
[0086] Examples of modified polydimethylsiloxanes containing OH and ether groups as organic substituents include products called polyether-modified polydimethylsiloxanes or polyether-modified silicones, where the polyether group ends in an OH group. Examples of commercially available products belonging to this category, where the ratio of polypropylene glycol repeating units to polyethylene glycol repeating units is less than 0.3, include products sold by Shin-Etsu Chemical Co., Ltd. such as X-22-4272 and KF-6123, but these are not limited to these. Furthermore, such polyether-modified polydimethylsiloxanes or polyether-modified silicones are sometimes named "PEG-(n)dimethylsiloxane" in cosmetic ingredient labeling. "PEG-(n)" refers to a PEG (polyethylene glycol) chain with n being the average corresponding number. "PEG-(n)dimethylsiloxane" is represented as "PEG-(n)DIMETHICONE" in the INCI nomenclature. Examples of commercially available products that fall into this category and whose ratio of the number of repeating units in propylene glycol to the number of repeating units in polyethylene glycol is less than 0.3 include PEG-9 dimethylsiloxane (product name: KF-6013), PEG-3 dimethylsiloxane (product name sold by Shin-Etsu Chemical Industry Co., Ltd.: KF-6015), PEG-10 dimethylsiloxane (product name sold by Shin-Etsu Chemical Industry Co., Ltd.: KF-6017), and PEG-10 dimethylsiloxane (product name sold by Shin-Etsu Chemical Industry Co., Ltd.: KF-6043), but are not limited to these.
[0087] Furthermore, for reactive silicones whose hydroxyl values are disclosed in product catalogs, it can be inferred that they are modified polydimethylsiloxanes containing OH groups and, where appropriate, ether groups as organic substituents. The hydroxyl value of the modified polydimethylsiloxane can be determined to confirm the presence of OH groups in the modified polydimethylsiloxane. In one embodiment, the modified polydimethylsiloxane has a hydroxyl value of 1 mg KOH / g or higher. The hydroxyl value can be determined, for example, by the method according to JIS K 0070 or by FT-NIR (near-infrared spectroscopy) according to JIS K 1557-6.
[0088] Alternatively, the presence of bending vibrations originating from the alcoholic OH group at approximately 1360–1340 cm⁻¹ can be determined by Fourier transform infrared spectroscopy (FT-IR) of modified polydimethylsiloxane. -1 The IR spectrum was used to confirm whether the organic substituents of the modified polydimethylsiloxane contained OH groups.
[0089] When the organic substituent includes an ether group, the ratio of the number of polypropylene glycol repeating units to the number of polyethylene glycol repeating units in the organic substituent can be determined based on the structure of the modified polydimethylsiloxane disclosed in product catalogs, etc. For example, if it is known that the modified polydimethylsiloxane contains OH and ether groups and does not contain polypropylene glycol repeating units, the ratio of the number of polypropylene glycol repeating units to the number of polyethylene glycol repeating units is 0, thus satisfying feature (b). In the absence of a specific structure, as described later for feature (c), the ratio can be determined based on the modified polydimethylsiloxane as measured in deuterated chloroform. 1 It can be calculated from the H NMR spectrum. Specifically, it can be based on the modified polydimethylsiloxane determined in deuterated chloroform. 1 The H NMR spectrum is calculated using the following formula (1), and the calculated value is regarded as the ratio of the number of repeating units of polypropylene glycol to the number of repeating units of polyethylene glycol.
[0090] Equation (1): [(Integral value of the signal in the range of 1.25 to 0.95 ppm) / 3] / {[(Integral value of the signal in the range of 4.4 to 3.2 ppm) - (Integral value of the signal in the range of 1.25 to 0.95 ppm)] / 4}
[0091] Some commercially available modified polydimethylsiloxanes do not disclose the detailed structure of the modifying groups. Additionally, some products are sold as surfactants, surface conditioners, leveling agents, defoamers, wetting agents, dispersants, and other additives; although they do not explicitly state that they are modified polydimethylsiloxanes and do not disclose their structure, they are still products belonging to the category of modified polydimethylsiloxanes. In this case, the modified polydimethylsiloxane measured in deuterated chloroform... 1 In the H NMR spectrum, substances that have a signal in the range of 0.3 to -0.3 ppm and 4.4 to 3.2 ppm, have or do not have a signal in the range of 1.25 to 0.95 ppm, have a signal that disappears due to the addition of D2O in the range of 13 to 0 ppm, and whose value calculated by the following formula (1) is less than 0.3 belong to the modified polydimethylsiloxane of this method (characteristic (c) above).
[0092] Equation (1): [(Integral value of the signal in the range of 1.25 to 0.95 ppm) / 3] / {[(Integral value of the signal in the range of 4.4 to 3.2 ppm) - (Integral value of the signal in the range of 1.25 to 0.95 ppm)] / 4}
[0093] The signal observed in the range of 0.3 to -0.3 ppm (hereinafter also referred to as the "first signal") originates from the hydrogen atom (-Si(C)) bonded to the carbon atom adjacent to the Si atom. H3 )2-) signal.
[0094] The signal observed in the range of 4.4–3.2 ppm (hereinafter also referred to as the “second signal”) originates from a hydrogen atom (e.g., -OC) attached to a carbon atom adjacent to the oxygen atom of an OH group or ether. H2 C H2 -O-、-OC H2 C H (CH3)-O-, -C H2 The signal of -OH).
[0095] The signal observed in the range of 1.25–0.95 ppm (hereinafter also referred to as the “third signal”) originates from the hydrogen atom of the methyl group in the polypropylene glycol chain, which is a polyether-modifying group (-CH2CH(C)). H3 The signal is )-O-).
[0096] It can be inferred that the signal observed in the range of 13–0 ppm and which disappears upon the addition of D₂O (hereinafter also referred to as the "4th signal") originates from O₂. H base or N H The signal of the hydrogen atom of the base.
[0097] The signal that disappears due to the addition of D₂O is typically observed in the range of 13–0 ppm. Among these, the signal observed in the range of 3–2 ppm and which disappears due to the addition of D₂O can be inferred to originate from O₂. H The signal of the hydrogen atom of the base.
[0098] The inference as to whether the signal that disappears due to the addition of D2O originates from the hydrogen atom of the OH group or the NH group can be made, for example, by the following methods.
[0099] Fourier transform infrared spectroscopy (FT-IR) determination
[0100] In the above 1 In addition to H NMR determination, Fourier transform infrared spectroscopy (FT-IR) of modified polydimethylsiloxane can also be used to observe whether there is a bending vibration of approximately 1360–1340 cm⁻¹ originating from the alcoholic OH radical. -1The IR spectrum was analyzed, leading to the conclusion that the signal that disappeared due to the addition of D2O originated from the hydrogen atoms of the OH group.
[0101] • Determination of acidity
[0102] In the above 1 Besides ¹H NMR determination, the acidity of modified polydimethylsiloxane can be used to infer whether the signal disappearing due to the addition of D₂O originates from the hydrogen atoms of the OH or NH groups. For example, 100 mg of the modified polydimethylsiloxane sample is dissolved in 200 μL of isopropanol, 200 μL of pure water is added, and the mixture is shaken thoroughly. The pH of the liquid is then measured. If the pH is between 3 and 7, it can be inferred that the signal disappearing due to the addition of D₂O originates from the hydrogen atoms of the OH groups. If the pH is above 8 (alkaline), it can be inferred that the signal disappearing due to the addition of D₂O originates from the hydrogen atoms of the NH groups.
[0103] In feature (c) above, the value calculated according to equation (1) is less than 0.3. Here, this value is shown below, and roughly corresponds to the ratio of the number of polypropylene glycol repeating units to the number of polyethylene glycol repeating units in the modified polydimethylsiloxane.
[0104] In equation (1), it is assumed that:
[0105] The signal observed in the range of 0.3 to -0.3 ppm (signal 1) is attributed to the dimethylsiloxane repeating unit -O-Si(C H3 The underlined hydrogen atom in 2-
[0106] The signal observed in the range of 4.4–3.2 ppm (the second signal) is attributed to the polyethylene glycol repeating unit -OC. H2 C H2 The underlined hydrogen atom in -O- and the repeating polypropylene glycol unit -OC H2 C H The underlined hydrogen atom in (CH3)-O-
[0107] The signal observed in the range of 1.25–0.95 ppm (signal 3) is attributed to the polypropylene glycol repeating unit -CH2CH(C H3 The underlined hydrogen atom is )-O-.
[0108] Under the above assumptions, when the integral value of the first signal, which is equivalent to 1 dimethylsiloxane repeating unit, is set to 6 and the integral value of each signal is calculated, the number of polypropylene glycol repeating units relative to 1 dimethylsiloxane repeating unit can be calculated by the following formula (2).
[0109] Equation (2): (Integral value of the third signal) / 3
[0110] Similarly, the number of polyethylene glycol repeating units relative to one dimethylsiloxane repeating unit can be calculated by the following formula (3).
[0111] Equation (3): [(Integral value of the second signal) - (Integral value of the third signal)] / 4
[0112] Based on the above equations (2) and (3), the ratio of the number of polypropylene glycol repeating units to the number of polyethylene glycol repeating units in the modified polydimethylsiloxane can be calculated by equation (1).
[0113] Equation (1): [(Integral value of the third signal) / 3] / {[(Integral value of the second signal) - (Integral value of the third signal)] / 4}
[0114] Examples of modified polydimethylsiloxanes that satisfy feature (c) include products sold by Shin-Etsu Chemical Industry Co., Ltd.: KF-945, X-22-4039, and products sold by Evonik Japan Co., Ltd.: TEGO TWIN 4000, TEGO TWIN 4100, etc.
[0115] In the polymerizable composition of this method, by including (C) a modified polydimethylsiloxane satisfying at least one of features (a), (b), and (c), overflow can be suppressed not only during thermosetting after coating onto a substrate or the like, but also during storage at room temperature. While not limited to this, the reason for suppressing overflow by including (C) the modified polydimethylsiloxane in the polymerizable composition can be considered as follows: When the polymerizable composition containing the modified polydimethylsiloxane is applied to a substrate or the like, due to the surface transfer properties of the modified polydimethylsiloxane, a portion of the modified polydimethylsiloxane is transferred to the coating surface of the polymerizable composition. Before other unreacted components permeate from the coating of the polymerizable composition, a very small amount of the modified polydimethylsiloxane transferred to the coating surface is transferred to the substrate, which is not in contact with the polymerizable composition, and the modified groups of the modified polydimethylsiloxane are adsorbed onto the substrate surface. It is believed that this forms an adsorption film of modified polydimethylsiloxane on the substrate surface. This film, due to its polydimethylsiloxane portion, exhibits water and oil resistance, thus inhibiting seepage. Furthermore, it is believed that by including COOH or OH groups in the organic substituents used as modifying groups, a higher adsorption effect of the modified polydimethylsiloxane onto the substrate can be obtained. Moreover, when the organic substituents used as modifying groups contain OH groups, since the amount of polypropylene glycol groups contained in the organic substituents is below a certain level, it is believed that the adsorption effect onto the substrate caused by the OH groups is not suppressed.
[0116] In one embodiment, the modified polydimethylsiloxane satisfying at least one of characteristics (b) and (c) is measured in deuterated chloroform. 1 In the H NMR spectrum, when the integral value of the first signal, which is equivalent to one dimethylsiloxane repeating unit, is set to 6 and the integral value of each signal is calculated, the integral value of the signal (second signal) observed in the range of 4.4 to 3.2 ppm is more preferably 0.3 to 19, and even more preferably 0.3 to 17.
[0117] 1 H NMR measurements can be performed under standard conditions. For example, 100 mg of the sample is dissolved in 500 μl of deuterated chloroform, and a 5 mm diameter filter is added. 1 The ¹H NMR sample tube was used for the measurement under the following conditions. After the measurement, 50 μl of heavy water (D₂O) was added to the sample tube, and the measurement was performed again under the same conditions. It was found that the signal that disappeared after adding heavy water came from the active hydrogen bonded to hydroxyl or amino groups.
[0118] Measurement frequency: 40–600 MHz
[0119] Solvent: Deuterated chloroform
[0120] Determining the type of nucleus: 1 H
[0121] Accumulated count: 4 to 80 times
[0122] Measurement temperature: 15~50℃
[0123] (C) Any one of the modified polydimethylsiloxanes may be used, or two or more may be used in combination.
[0124] (C) The content of modified polydimethylsiloxane relative to the total mass of the polymerizable composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. Furthermore, it is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less. In one embodiment, the content of (C) modified polydimethylsiloxane relative to the total mass of the polymerizable composition is preferably 0.01 to 5% by mass, more preferably 0.1 to 4% by mass, and even more preferably 0.2 to 3% by mass.
[0125] If necessary, the polymerizable composition of this method may also contain any component other than the components (A) to (C) mentioned above, for example, the components described below.
[0126] (D) Packing
[0127] The polymerizable composition of this method may contain (D) filler (hereinafter also referred to as "component (D)") to a extent that does not impair the effects of the present invention. By containing (D) filler in the polymerizable composition, the coefficient of linear expansion of the cured product obtained by curing the polymerizable composition can be reduced, and the thermal cycling resistance can be improved. In addition, if the filler is of low elastic modulus, the stress generated in the cured product can be relieved, and the long-term reliability can be improved. (D) filler is generally divided into inorganic filler and organic filler.
[0128] Inorganic fillers are formed from granular bodies of inorganic materials. There are no particular limitations on any inorganic filler that reduces the coefficient of linear expansion through addition. Suitable inorganic materials include silica, talc, alumina, aluminum nitride, calcium carbonate, aluminum silicate, magnesium silicate, magnesium carbonate, barium sulfate, barium carbonate, lime sulfate, aluminum hydroxide, calcium silicate, potassium titanate, titanium dioxide, zinc oxide, silicon carbide, silicon nitride, and boron nitride. Any one type of inorganic filler can be used, or two or more can be used in combination. Silica filler is preferred from the perspective of increasing the filler volume. Amorphous silica is preferred.
[0129] The surface of the inorganic filler can be treated with coupling agents such as silane coupling agents. This allows the viscosity of the polymerizable composition to be set within an appropriate range.
[0130] Examples of organic fillers include polytetrafluoroethylene (PTFE) fillers, silicone fillers, acrylic fillers, and styrene fillers. Organic fillers can be surface-treated. The glass transition temperature of organic fillers is preferably higher than 40°C.
[0131] The shape of the filler is not particularly limited and can be any of the following: spherical, scaly, needle-like, or amorphous.
[0132] In one embodiment, the average particle size of the filler is preferably 5.0 μm or less, more preferably 4.0 μm or less, and even more preferably 3.0 μm or less. In this specification, the term "average particle size" refers to the median diameter (d50) of a volume reference determined by laser diffraction according to ISO-13320 (2009), or the arithmetic mean of 50 measurements arbitrarily selected from observation images obtained using a transmission electron microscope (TEM) or a scanning electron microscope (SEM). By setting the average particle size of the filler to the upper limit or below, filler sedimentation can be suppressed, and the formation of coarse particles can be suppressed, as can clogging of the nozzle of the sizing machine. The lower limit of the average particle size of the filler is not particularly limited; however, from the viewpoint of the viscosity of the polymerizable composition, it is preferably 0.005 μm or more, more preferably 0.1 μm or more. In one embodiment of this approach, the average particle size of the filler is preferably 0.01 μm to 5.0 μm, more preferably 0.1 μm to 3.0 μm. Fillers with different average particle sizes can also be used in combination. For example, fillers with an average particle size of 0.005 μm or more but less than 0.1 μm and fillers with an average particle size of 0.1 μm to 5.0 μm can be used in combination.
[0133] The content of (D) filler in the polymeric composition of this method is preferably 0.5 to 80% by mass relative to the total mass of the polymeric composition, more preferably 1 to 70% by mass, and even more preferably 3 to 60%. By setting the content of (D) filler to the above range, the heat resistance cycling performance is improved, and the viscosity of the polymeric composition is set to an appropriate range, thereby improving its applicability in a sizing machine.
[0134] Photosensitizer
[0135] If desired, the polymerizable composition of this method may also contain a photosensitizer, to the extent that it does not impair the effects of the invention. The photosensitizer is capable of absorbing light energy and transferring it to the acid-producing agent, thereby increasing the light sensitivity of the acid-producing agent. Examples of photosensitizers include thioxanthone derivatives, carbonyl compounds, organosulfur compounds, persulfides, redox compounds, azo and diazo compounds, halogen compounds, photoreducing pigments, etc., but are not limited to them.
[0136] Any one photosensitizer may be used, or two or more may be used in combination. When the polymerizable composition of this method contains a photosensitizer, the photosensitizer content relative to the total mass of the acid-producing agent is preferably 0.1 to 1000% by mass, more preferably 1 to 500% by mass.
[0137] Photoradix initiators
[0138] If desired, the polymerizable composition of this method may also contain a photoradical initiator, within a range that does not impair the effects of the invention. The photoradical initiator absorbs light to generate free radicals as active species, which reduce and decompose the acid-producing agent, promoting the release of acid from the acid-producing agent. Examples of photoradical initiators include alkyl phenyl ketone compounds, acylphosphine oxide compounds, oxime ester compounds, and compounds having photosensitive sites and peroxide structures, but are not limited to these.
[0139] One or more photoradical initiators can be used. When the polymerizable composition of this method contains a photoradical initiator, the content of the photoradical initiator relative to the total mass of the acid-producing agent is preferably 10-200% by mass, more preferably 50-150% by mass.
[0140] Thermal free radical initiators
[0141] If desired, the polymerizable composition of this method may also contain a thermal free radical initiator, within a range that does not impair the effects of the invention. A thermal free radical initiator can generate active species free radicals by cleaving at a given temperature, reducing the acid-producing agent and promoting the release of acid from the acid-producing agent. Examples of thermal free radical initiators include organic peroxides, inorganic peroxides, azo compounds, etc.
[0142] The thermal free radical initiator can be any one type, or two or more types can be used in combination. When the polymerizable composition of this method contains a thermal free radical initiator, the content of the thermal free radical initiator relative to the total mass of the acid-producing agent is preferably 1 to 200% by mass, more preferably 10 to 150% by mass.
[0143] Free radical polymeric compounds
[0144] The polymerizable composition of this method may include free radical polymerizable compounds without impairing the effects of the invention. In the case of certain types of acid-producing agents, active free radicals are also generated, thus promoting the free radical polymerization of the free radical polymerizable compound and imparting curability and adhesiveness to the polymerizable composition. Examples of free radical polymerizable compounds include compounds with unsaturated double bonds such as (meth)acrylate compounds, bismaleimide compounds, styrene compounds, and polybutadiene compounds, or mixtures of compounds with unsaturated double bonds and thiols (mixtures capable of undergoing ene-thiol reactions), but are not limited to these. Any one free radical polymerizable compound may be used, or two or more may be used in combination.
[0145] Other additives
[0146] The polymerizable composition may also contain other additives as needed, without prejudice to the purpose of this method, such as stabilizers, coupling agents, carbon black, titanium black, ion traps, leveling agents, antioxidants, defoamers, thixotropic agents, viscosity modifiers, flame retardants, etc.
[0147] From the viewpoint of suppressing VOC emissions and inhibiting the shrinkage of cured products, the polymerizable composition of this method preferably does not contain solvents substantially. In this specification, "the polymerizable composition does not contain solvents substantially" means that the solvent content in the polymerizable composition is less than 1% by mass relative to the total mass of the polymerizable composition. Examples of solvents include hydrocarbons (benzene, toluene, xylene, cyclohexane, etc.), aprotic polar solvents (N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc.), nitriles (acetonitrile, etc.), ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), esters (ethyl acetate, butyl acetate, butyrolactone, propylene carbonate, etc.), ethers (cyclopentyl methyl ether, diethyl ether, tetrahydrofuran, dimethoxyethane, etc.), alcohols (methanol, ethanol, propanol, butanol, etc.), terpenes (turpentine, terpineol, isobornyl acetate, etc.), and halogen solvents (dichloromethane, chloroform, etc.), which are commonly used organic solvents in the field of curable compositions.
[0148] The viscosity of the polymerizable composition in this method is preferably 0.5 to 100 Pa·s. The viscosity can be appropriately adjusted according to the application and site of the polymerizable composition. In this specification, unless otherwise specified, the viscosity of the composition is expressed as a value measured according to Japanese Industrial Standard JIS K6833. Specifically, it can be determined using an E-type viscometer at a rotation speed of 10 rpm. There are no particular limitations on the equipment, rotor, or measuring range used.
[0149] Polymerizable compositions can be obtained, for example, by simultaneously or separately heating and stirring, melting, mixing, and / or dispersing components (A) to (C), and other components as needed, either as required. There are no particular limitations on the apparatus used for these mixing, stirring, and dispersing operations. Suitable apparatuses include pulverizers equipped with stirring and heating devices, Henschel mixers, three-roll mills, ball mills, planetary mixers, and bead mills. Furthermore, these apparatuses can be appropriately combined.
[0150] The polymeric composition of this method can be formulated as a one-liquid polymeric composition that is contained in a single container, or as a two-liquid (or multi-liquid) polymeric composition that is contained in two or more containers, depending on its intended use. When formulating a two-liquid (or multi-liquid) polymeric composition, the aforementioned components (A) to (C), and any other components used as needed, can be selected in the same manner as in the one-liquid composition. Furthermore, when formulating a two-liquid (or multi-liquid) polymeric composition, the aforementioned components (A) to (C), and any other components used as needed, can be divided into two or more liquids in any distribution manner without particular restriction. When divided into two or more liquids in any distribution manner, each liquid may contain one or more components selected from the aforementioned components (A) to (C) and any other components used as needed; a single liquid may contain the aforementioned components (A) to (C); or a liquid may consist only of the aforementioned components (A) to (C) and / or any other components used as needed. For example, when the composition consists of liquid A and liquid B, the distribution can be as follows: liquid A: component (A), liquid B: component (B) and component (C); liquid A: component (A) and component (C), liquid B: component (B); liquid A: component (A) and component (C), liquid B: component (B) and component (C); liquid A: component (A), liquid B: component (B) and component (C) and component (D); liquid A: component (A) and component (C), liquid B: component (B) and component (D); liquid A: component (A) and component (D), liquid B: component (B) and component (C). When components (A) to (C) are included in liquid A and all other components are included in liquid B, liquid A alone, or liquid A and liquid B together, can be considered as a polymerizable composition of this method. On the other hand, when components (A) to (C) are each included in different liquids, each liquid can be considered as a polymerizable composition of this method. As an example of the above components (A) to (C) being contained in different liquids, a polymeric composition can be provided in which the above components (A) to (C) are dispensed into two or more containers. Specifically, a kit formed from multiple liquids containing any one of the above components (A) to (C) can be provided.
[0151] The resulting polymeric composition can exhibit photocurability, thermocurability, or both photocurability and thermocurability depending on the type of acid-producing agent contained in the composition. Photocuring of the polymeric composition is performed, for example, by irradiating the composition with UV light. Thermocuring of the polymeric composition is performed, for example, at a temperature of 100°C. Regarding the thermocuring temperature of the polymeric composition, in the case of manufacturing semiconductor modules (e.g., optical sensor modules such as camera modules) containing components where the polymeric composition deteriorates under high-temperature conditions, 60–90°C is preferred. The thermocuring time, while depending on other curing conditions, can be, for example, 30–120 minutes. In the case of a photocurable and thermocurable polymeric composition, for example, it can be pre-cured by light-based (UV) curing and then formally cured by heat-based curing.
[0152] The polymeric composition of this method can be used, for example, as an adhesive, sealant, damming agent, or raw material for fixing, bonding, or protecting components, and is suitable for formulation into a liquid form. Here, the damming agent is pre-formed on the outer periphery of a substrate before sealing multiple semiconductor chips or the like with a low-viscosity filler. By forming a dam using this damming agent, the outflow of the low-viscosity filler used to seal the multiple semiconductor chips can be suppressed. Furthermore, adhesives containing the polymeric composition of this method can achieve good bonding with engineering plastics, ceramics, and metals.
[0153] The coating method for the polymeric composition is not particularly limited. For example, it can be applied to the desired portion of a component, such as a substrate, by known printing, dispensing, or coating methods. Examples of printing methods include inkjet printing, screen printing, offset printing, carton printing, metal printing, flexographic printing, gravure printing, and so on, but are not limited to these. Examples of dispensing methods include using a jet dispensing machine, a pneumatic dispensing machine, etc., but are not limited to these. Examples of coating methods include dip coating, spray coating, bar coating, gravure coating, reverse gravure coating, spin coating, etc., but are not limited to these. In one embodiment, the coating method for the polymeric composition is preferably the method using a pneumatic dispensing machine.
[0154] [Adhesive or sealant]
[0155] An adhesive or sealing material, as one aspect of the present invention, comprises a polymeric composition as described above. This adhesive or sealing material can effectively fix, bond, or protect general-purpose plastics (e.g., PE, PS, PP, etc.), engineering plastics (e.g., LCP (liquid crystal polymer), polyamide, polycarbonate, etc.), ceramics (e.g., alumina, aluminum nitride, beryllium oxide, etc.), and metals (e.g., copper, nickel, etc.), and can be used for fixing, bonding, or protecting components constituting semiconductor devices or electronic components. Examples of semiconductor devices include, but are not limited to, HDDs, semiconductor elements, optical sensor modules, other semiconductor modules, integrated circuits, etc. The adhesive or sealing material of this aspect is preferably used for fixing, bonding, or protecting components constituting optical sensor modules such as camera modules.
[0156] The adhesive or sealant of this method can be formulated as a one-component adhesive or sealant that can be contained in a single container, or as a two-component (or multi-component) adhesive or sealant that can be contained in two or more containers, depending on its intended use. When formulating a two-component (or multi-component) adhesive or sealant, the aforementioned components (A) to (C), and any other components used as needed, can be selected in the same manner as in the one-component type. Furthermore, when formulating a two-component (or multi-component) adhesive or sealant, the aforementioned components (A) to (C), and any other components used as needed, can be divided into two or more components in any manner without particular restriction. When divided into two or more components in any manner, each liquid may contain one or more components selected from the aforementioned components (A) to (C) and any other components used as needed; a single liquid may contain the aforementioned components (A) to (C); or a liquid may consist only of the aforementioned components (A) to (C) and / or any other components used as needed. For example, when the mixture consists of liquid A and liquid B, the distribution can be as follows: liquid A: component (A), liquid B: component (B) and component (C); liquid A: component (A) and component (C), liquid B: component (B); liquid A: component (A) and component (C), liquid B: component (B) and component (C); liquid A: component (A), liquid B: component (B) and component (C) and component (D); liquid A: component (A) and component (C), liquid B: component (B) and component (D); liquid A: component (A) and component (D), liquid B: component (B) and component (C). When components (A) to (C) are included in liquid A, and all other components are included in liquid B, liquid A alone, or liquid A and liquid B together, can be considered as the adhesive or sealant of this method. On the other hand, when the aforementioned components (A) to (C) are contained in different liquids, each liquid can be considered as an adhesive or sealing material of this method. As an example of the aforementioned components (A) to (C) being contained in different liquids, an adhesive or sealing material constructed by dispensing the aforementioned components (A) to (C) into two or more containers can be cited as an example. Specifically, a kit formed from multiple liquids containing any of the aforementioned components (A) to (C) can be cited as an example.
[0157] [Cure of polymeric compositions, adhesives, or sealants]
[0158] Another aspect of the cured product is a cured product obtained by curing the polymeric composition described above or the adhesive or sealant described above. In the area surrounding the adherend to which this cured product is bonded, seepage is suppressed.
[0159] [Semiconductor devices, electronic components]
[0160] One aspect of the present invention comprises a semiconductor device or electronic component comprising a cured product of the above-described manner. Here, "semiconductor device" refers to any device capable of functioning by utilizing the properties of semiconductors, including electronic components, semiconductor circuits, modules assembled thereon, electronic devices, etc. Examples of semiconductor devices or electronic components include HDDs, semiconductor elements, optical sensor modules, other semiconductor modules, integrated circuits, etc., but are not limited to these. Examples of optical sensors include photodiodes, photoelectric integrated circuits, photomultiplier tubes (PMTs), phototubes, image sensors, beam splitters / spectral sensors, infrared sensors, ultraviolet / flame sensors, X-ray sensors, radiation sensors, electron / ion sensors, distance / position sensors, etc., but are not limited to these.
[0161] Example
[0162] The present invention will be further described in detail below using embodiments and comparative examples; however, the present invention is not limited to these embodiments. It should be noted that in the following embodiments, unless otherwise specified, parts and percentages refer to parts by mass and percentage by mass.
[0163] [Preparation of Polymerizable Compositions]
[0164] The polymeric compositions of the Examples and Comparative Examples were prepared by mixing the given amounts of each component using a three-roll mill according to the formulations shown in Tables 2-1 to 2-5. In Tables 2-1 to 2-5, the amount of each component is expressed in parts by mass (in g). The components used in the Examples and Comparative Examples are shown below.
[0165] (A) Cationic polymeric compounds
[0166] (A-1): Hydrogenated bisphenol A diglycidyl ether (product name: jER YX8000, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 205g / eq)
[0167] (A-2): Special epoxy resin (Product name: AER9000, manufactured by Asahi Kasei Corporation, polyether type epoxy, epoxy equivalent: 380g / eq)
[0168] (A-3): 3,4-Epoxycyclohexylmethyl-3,4-Epoxycyclohexane carboxylate (Product name: CELLOXIDE (registered trademark) 2021P, manufactured by Daicel Co., Ltd., alicyclic epoxy, epoxy equivalent: 130g / eq)
[0169] (A-4): 1,2-Epoxytetradecane (Product name: TD-EX, manufactured by Yokkaichi Synthetic Co., Ltd., monofunctional epoxy, epoxy equivalent: 212 g / eq)
[0170] (A-5): Special epoxy resin (product name: HiREM-2, manufactured by Shikoku Kasei Corporation, epoxy equivalent: 80g / eq)
[0171] (A-6): 3-Ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane (Product name: OXT-221, manufactured by Toa Synthetic Co., Ltd., oxetane equivalent: 107 g / eq)
[0172] • (B) Acid-producing agent
[0173] (B-1): 4-Isopropyl-4'-methyldiphenyliodonium tetra(pentafluorophenyl)borate (Product name: BLUESIL (registered trademark) PI 2074, manufactured by ELKEM SILICONES, photoacid generator)
[0174] (B-2): Sulfonium salt-based acid generator (Product name: VC-1FG, manufactured by San-Apro Co., Ltd., photoacid generator)
[0175] (B-3): Borate quaternary ammonium salt (Product name: CXC-1821, manufactured by King Industries, Inc., thermal acid generator)
[0176] • (C) Modified polydimethylsiloxane (Component (C))
[0177] • Modified polydimethylsiloxane other than component (C) (component (C'))
[0178] As components (C) and (C'), the modified polydimethylsiloxanes listed in Table 1 below are used. Various modified polydimethylsiloxanes are subjected to deuterated chloroform... 1 The results of H NMR determination, Fourier transform infrared spectroscopy (FT-IR) determination, and acidity determination are shown in Table 1.
[0179] [Table 1]
[0180]
[0181] In Table 1, “Ph” represents phenyl and “Me” represents methyl.
[0182] In Table 1, “[(3rd signal) / 3] / {[(2nd signal)-(3rd signal)] / 4}” represents the integral value of the signal in the range of 1.25 to 0.95 ppm in equation (1) as [(integral value of the signal in the range of 4.4 to 3.2 ppm)-(integral value of the signal in the range of 1.25 to 0.95 ppm)] / 4}.
[0183] • (D) Filler (Composition (D))
[0184] (D-1): Surface-treated silica filler (product name: SE5200SEE, average particle size 2μm, manufactured by Adamatechs Co., Ltd.)
[0185] (D-2): Silica filler (Product name: CAB-O-SIL (registered trademark) TS-720, polydimethylsiloxane surface-treated pyrolysis silica, manufactured by Cabot Corporation)
[0186] (E) Any other components
[0187] (E-1): Dihexadecyl peroxide (product name: Perkadox24L, manufactured by Norinon Chemical Co., Ltd., thermal free radical initiator)
[0188] (E-2): 2,4-Diethylthioxanthone (DETX) (photosensitizer)
[0189] [Modified polydimethylsiloxane] 1 [H NMR determination]
[0190] Dissolve 100 mg of the test sample of various modified polydimethylsiloxanes in 500 μL of deuterated chloroform, and add a 5 mm diameter... 1 The H NMR sample tube was used for the determination under the following conditions. After the determination, 50 μL of heavy water (D2O) was added to the sample tube, and the determination was performed again under the same conditions. The signals from chloroform in the range of 0.3 to -0.3 ppm were integrated, and the integrated values of each signal are shown in Table 1 with the obtained value set to 6.
[0191] Measuring apparatus: Oxford instrument Pulsar HF
[0192] Measurement frequency: 60 MHz
[0193] Solvent: Deuterated chloroform
[0194] Determining the type of nucleus: 1 H
[0195] Measurement temperature: 37℃
[0196] Total number of times: 32
[0197] The assignment examples of each signal under the above measurement conditions are shown below.
[0198] 0.3 to -0.3 ppm: originates from hydrogen atoms (-Si(C)) bonded to carbon atoms adjacent to Si atoms. H3)2-) signal
[0199] 4.4–3.2 ppm: Derived from hydrogen atoms attached to the carbon atom adjacent to the oxygen atom of the OH group or ether (e.g., -OC). H2 C H2 -O-、-OC H2 C H (CH3)-O-, -C H2 The signal of -OH)
[0200] 1.25–0.95 ppm (d, approx. 6 Hz): from hydrogen atoms of the methyl group in the polypropylene glycol chain (-CH2CH(C)). H3 () -O-) signal
[0201] Under the above measurement conditions, the signal that appeared in the range of 9.0–0.5 ppm and disappeared upon the addition of D₂O originated from O₂. H base or N H Signal of the hydrogen atom of the base
[0202] [Determination of modified polydimethylsiloxane by Fourier transform infrared spectroscopy (FT-IR)]
[0203] Under the following conditions, Fourier transform infrared spectroscopy (FT-IR) was performed on various modified polydimethylsiloxanes to confirm the C=O stretching vibration of carboxylic acid (approximately 1715 cm⁻¹). -1 The presence or absence of OH and the bending vibration of alcoholic OH (approximately 1360–1340 cm). -1 The presence or absence of ) is shown in Table 1.
[0204] Measurement apparatus: Perkin-Elmer FT-IR Spectrometer Spectrum 3
[0205] Measurement method: ATR method
[0206] [Acidity determination of modified polydimethylsiloxane]
[0207] 100 mg of various modified polydimethylsiloxane samples were dissolved in 200 μL of isopropanol (IPA), 200 μL of pure water was added, and the mixture was shaken thoroughly. pH test paper was then immersed in the resulting liquid to determine the pH. Macherey Nagel #90204 general-purpose pH test paper was used. The results are shown in Table 1.
[0208] In the examples and comparative examples, the properties of the polymeric compositions were determined as follows.
[0209] [Leakage Assessment]
[0210] The polymeric compositions of the examples and comparative examples were applied in 1.5 mg doses using a dispensing machine to a ceramic substrate that had undergone plasma treatment with argon (Ar) gas. The overflow lengths (N = 3 pcs × 2 sides) under two conditions were measured using a CCD camera. The results are shown in Tables 2-1 to 2-5. Condition 1: The overflow length on the ceramic substrate after application to room temperature (20°C–25°C) for 60 minutes. Condition 2: The overflow length on the ceramic substrate after application to room temperature (20°C–25°C) for 60 minutes, followed by thermosetting of the polymeric composition at 80°C for 60 minutes.
[0211] It should be noted that, regarding the overflow length shown in Tables 2-1 to 2-5, since 3000 μm is the measurement limit for overflow length, samples with overflow length exceeding the measurement limit are recorded as >3000 μm.
[0212]
[0213]
[0214]
[0215]
[0216]
[0217] It can be seen that the polymerizable compositions of modified polydimethylsiloxane containing at least one of features (a), (b) and (c) of Examples 1 to 19 significantly suppressed the overflow phenomenon under conditions 1 and 2 compared with the polymerizable compositions of Comparative Examples 1, 7 to 11 that do not contain modified polydimethylsiloxane (C) and the polymerizable compositions of Comparative Examples 2 to 6 that contain modified polydimethylsiloxane other than component (C').
[0218] Industrial availability
[0219] The present invention relates to polymeric compositions that are at least photocurable or thermocurable and capable of suppressing leakage, and are particularly useful as adhesives or sealants used for fixing, bonding or protecting components of miniaturized or highly integrated semiconductor modules.
[0220] The entire contents of the disclosure of Japanese Patent Application No. 2024-056011 (filed on March 29, 2024) are incorporated herein by reference.
[0221] All documents, patent applications and technical standards described in this specification are incorporated herein by reference to the same extent as the specific and individually described documents, patent applications and technical standards are incorporated herein by reference.
Claims
1. A polymerizable composition comprising: (A) Cationic polymeric compounds, (B) Acid-producing agents, and (C) A modified polydimethylsiloxane that satisfies at least one of the following characteristics (a), (b), and (c): (a) Organic substituents containing COOH groups are directly bonded to polydimethylsiloxane, or are bonded to polydimethylsiloxane through linking groups; (b) An organic substituent containing an OH group and, where appropriate, an ether group, is directly bonded to polydimethylsiloxane or bonded to polydimethylsiloxane via a linking group, wherein, in the case of an ether group, the ratio of the number of polypropylene glycol repeating units in the organic substituent to the number of polyethylene glycol repeating units is less than 0.
3. (c) Detected in deuterated chloroform 1 In the H NMR spectrum, a signal is present in the ranges of 0.3ppm to -0.3ppm and 4.4ppm to 3.2ppm, a signal is present or absent in the range of 1.25ppm to 0.95ppm, and a signal that disappears due to the addition of D2O is present in the range of 13ppm to 0ppm. Furthermore, the value calculated using the following formula (1) is less than 0.3: Equation (1): [(Integral value of signal in the range of 1.25ppm to 0.95ppm) / 3] / {[(Integral value of signal in the range of 4.4ppm to 3.2ppm) - (Integral value of signal in the range of 1.25ppm to 0.95ppm)] / 4}.
2. The polymerizable composition according to claim 1, wherein, The (A) cationic polymerizable compound includes compounds having an epoxy group and compounds having an oxocyclic butyl group.
3. The polymerizable composition according to claim 1 or 2, wherein, The content of the (C) modified polydimethylsiloxane is 0.01% to 5% by mass relative to the total mass of the polymeric composition.
4. The polymerizable composition according to any one of claims 1 to 3, It further includes (D) filler.
5. The polymerizable composition according to any one of claims 1 to 4, wherein, The components (A) to (C) are constituted in a single container.
6. The polymerizable composition according to any one of claims 1 to 4, wherein, The components (A) to (C) are prepared by dispensing them in two or more containers.
7. An adhesive or sealant, It comprises the polymeric composition according to any one of claims 1 to 6.
8. The adhesive or sealant according to claim 7, It is used for fixing, bonding, or protecting optical sensor modules or the components that make up them.
9. A cured product obtained by curing the polymeric composition of any one of claims 1 to 6, or the adhesive or sealant of claim 7 or 8.
10. A semiconductor device or electronic component comprising the cured material of claim 9.
11. The semiconductor device or electronic component according to claim 10, wherein it is an optical sensor module.
Citation Information
Patent Citations
Dual-curing adhesive composition
JP2021147584A
Information processor
JP2024056011A